(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Employment and unemployment are two opposing, mutually exclusive concepts, and the higher the employment rate, the lower the unemployment rate, and vice versa. Full employment of the population does not mean that unemployment does not exist at all, because it is almost impossible to eliminate unemployment